(untitled) (Texas Journal of Medical Science, 2025)
Nicotine leukoceratosis of the palate, associated with the use of electronic cigarettes (vaping), is becoming an increasingly urgent problem in dentistry and oncology. The article presents the clinical features of the disease in patients from different regions, as well as the results of a study on the effectiveness of improved therapeutic and preventive methods. 160 patients from Uzbekistan, Europe, Russia, the USA and Korea were included. Data on the prevalence of the disease, pathogenesis, and treatment outcomes are analyzed. A comprehensive approach is proposed, including topical treatment, immunomodulation, and vaping cessation programs, which significantly improves clinical outcomes and reduces the risk of leukoceratosis progression